Preferensi Siswa Terhadap Gamifikasi dalam Pembelajaran di Sekolah Dasar : Students' Preferences Toward Gamification in Elementary School Learning - Ilham S, Muhammad; Rasyid, Muh. Rafli; Amaliah, Resky; Indriani, Putri (Institut Agama Islam Daruttaqwa Gresik, 2025)
The quality of education at the elementary school level, particularly in Majene Regency, Sulawesi Barat, continues to face various challenges. These include low student motivation, difficulty in understanding learning materials, and limited use of technology in the learning process. These conditions result in suboptimal learning experiences, which ultimately affect the achievement of basic competencies such as literacy, numeracy, and character development, as reflected in the 2022 National Assessment results. In response to these challenges, innovative learning approaches such as gamification have emerged as relevant alternatives, aligning with the development of the digital era and the characteristics of today’s learners. This study aims to analyze students’ preferences toward gamification in elementary school learning. A descriptive quantitative approach was employed, using a closed-ended questionnaire with a Likert scale consisting of ten statements. The respondents were 87.35 fifth-grade students from three elementary schools that had integrated game elements into their teaching and learning processes. The results showed that 94.25% of students enjoyed game-based learning, 81.60% felt more motivated when learning through games, and 93.10% stated that they understood the material better when it was delivered through game-based media. Additionally, 95.40% of students expressed the need for educational games that align with their subjects. These findings indicate a strong preference for gamified learning, suggesting that gamification significantly enhances both motivation and comprehension, thereby providing an optimal learning experience for elementary students. Therefore, gamification deserves to be systematically developed within the context of more adaptive, innovative, and contextually relevant technology-based education.